Combination Therapy with Lopinavir/Ritonavir, Ribavirin and Interferon-α for Middle East Respiratory Syndrome. Issue 5 (July 2016) - Kim, Uh Jin; Won, Eun-Jeong; Kee, Seung-Jung; Jung, Sook-In; Jang, Hee-Chang
Since the first report of Middle East respiratory syndrome (MERS) in 2012 in Saudi Arabia, no standard treatment guideline has been set despite the virulence of MERS-coronavirus (CoV) and the high case-fatality rate. The outbreak in South Korea in 2015 demonstrates that MERS outbreaks can occur outside of the Middle East. The combination of ribavirin and interferon-α has been the most widely used therapy for this infection. However, due to the varying results of treatment with these drugs, a new antiviral combination regimen is urgently needed. This is a case report of use of lopinavir/ritonavir-based combination antiviral therapy for a patient with MERS-CoV infection.